PROMOTING INDONESIAN LOCAL WISDOM THROUGH LITERARY CRITICISM - M. Khalid, Irpan Apandi Batubara, (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2016)
The new curriculum of English language teaching in Indonesia urges students contribute actively to world networking as well as to world civilization. In the curriculum, students are introduced to the genre of text. As film is a representation of narrative text, writing a literary criticism can be one way to promote indonesia culture. This research is a content analysis on batak film Anak Sasada. As a modern literary work, the film contain local wisdom as part of culture that is potential to be introduced to world community and literary criticism in English is a way of promoting it. Martarombo is a local wisdom of Batak that found in the film of Anak Sasada.